Penegakan Hukum Pungutan Liar di Jawa Barat dalam Pelayanan Publik Pasca Covid-19 - Mahmud, Ade (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research analyzes the urgency of developing electronic-based public services in preventing criminal acts of illegal levies (extortion) to support transparent and good quality government governance and offers ideas for law enforcement to eradicate extortion, which is remains considerably lacking in West Java Province, especially after Covid-19. Hence the problem formulation focuses on the issue of how to develop public services to prevent the practice of extortion and how to build law enforcement to eradicate extortion in West Java Province. This paper is normative legal research using statutory approach and conceptual approaches that uses secondary data in the form of books, law journals, research reports, magazines, statutory regulations, and recapitulation of agency performance data to produce accurate and accountable conclusions. The results of the research conclude that the development of electronic-based services can be realized by changing manual services to digital ones, upgrading digital services with new features that accommodate people's needs, increasing e-money payments that are connected to the banking system followed by developing the Public Service Mall (MPP) concept that is accessible to the public. Law enforcement overcomes extortion by building reporting system connectivity that is directly connected between SiBerli and the extortion reporting system in agencies/institutions/units providing public services, implementing a reward and punishment system objectively as well as applying administrative sanctions for officials who abuse their authority and criminal sanctions as the ultimum remedium if other legal instruments are unable to resolve the crisis.Keywords: Development, Illegal Extortion, Law Enforcement. AbstrakPenelitian ini menganalisis urgensi pengembangan pelayanan publik berbasis elektronik dalam mencegah tindak pidana pungutan liar (pungli) untuk mendukung tata kelola pemerintahan yang bersih berkualitas dan menawarkan gagasan penegakan hukum pemberantasan pungli yang dinilai masih cukup lemah di Provinsi Jawa Barat terutama pasca covid-19 sehingga rumusan masalah berfokus pada persoalan bagaimana pengembangan layanan publik mencegah praktik pungli dan bagaimana membangun penegakan hukum dalam memberantas pungli di Provinsi Jawa Barat. Tulisan ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual yang memakai data sekunder berupa buku, jurnal hukum, laporan penelitian, majalah, peraturan perundang-undangan, rekapitulasi data kinerja instansi untuk menghasilkan simpulan yang akurat dan akuntabel. Hasil penelitian menyimpulkan bahwa pengembangan layanan berbasis elektronik dapat direalisasikan dengan mengubah pelayanan manual ke digital, meng-upgrade layanan digital dengan fitur baru yang mengakomodir kebutuhan masyarakat, peningkatan pembayaran e-money yang terhubung dengan sistem perbankan diikuti pengembangan konsep Mall Pelayanan Publik (MPP) yang mudah dijangkau masyarakat. Penegakan hukum mengatasi pungli dengan membangun konektivitas sistem pelaporan yang terhubung langsung antara SiBerli dengan sistem pelaporan Pungli di Badan/Lembaga/Unit pemberi layanan publik, menerapkan sistem reward and punishment secara objektif. Menerapkan sanksi administratif bagi aparatur yang menyalahgunakan wewenang dan sanksi pidana sebagai ultimum remedium apabila instrumen hukum lain tidak mampu menyelesaikan.Kata Kunci: Penegakan Hukum, Pengembangan, Pungutan Liar.